PENGUJIAN TEST CASE UNTUK PENGOLAHAN DATA KARYAWAN BERBASIS MULTI USER - Suhada, Sitti (Sainstek, 2008)
This research aim to the examination of system of data processing of employee on the multi user by using method test of case. Software examination specially method test the case own the high probabilitas to find the mistake, more careful and aacurate so that is not happened by the redudansi in course of data processing student. Research method used by study of book and software examination test the case with the approach of white box testing and bases path testing. Result of research by using method test of case can yield the system and process the restating of at flowchart of input of data processing of employee on the multi user making system become efficient and effective anf also system of data processing of employee on the multi user can yield the quality of information system become better.